Determination of Lipid and Alkaloid Content in some Medicinal Plants of Genus Sesbania - V.B.Kadam2, R.K.Momin1* and (Journal of Ecobiotechnology, 2011)
The seasonal variation of alkaloids have been investigated in leaf, bark and wood of Sesbania grandiflora, Sesbania bispinosa and Sesbania cannabina which are medicinally important in Marathwada region .The leaves of Sesbania grandiflora showed high level of Lipid(range 29.75 to 33.75mg/g dry wt.) than Sesbania bispinosa and Sesbania cannabina ( 22.95 to 27.85 and 21.85 to 23.60 mg/g dry wt.) respectively. The leaves of Sesbania grandiflora showed high level of (3.7 to 4.6 mg/g dry wt.) alkaloid than Sesbania bispinosa and Sesbania cannabina (3.4 to 3.75 and 2.15 to 2.75 mg/g dry wt.) respectively.